(untitled) (Journal of Engineering and Health Sciences, 2022)
Occupational safety, health and environment (OSHE) in school framework is aim to design a safe school concept in order to minimize the incident cases that happened in school area. This framework is very useful if it is implemented in every school. In turn, it can also improve safety and health features in the future. With the existence of this framework of occupational safety, health and environment (OSHE), will give an idea in safety emphasizing safety and health in schools, especially in safety management and also in the physical environment factors. Based on survey carried out by 50 respondents that are from the residents of school, one of the major problems regarding the occupational safety and health in school is because of the lack of safety management and physical environment in school. In order to get the confirmation about this, the survey was conducted to 50 targeted respondents. The result from the survey shown that they agreed that the aspect of safety and health is very vital to adapt in school. In advance they also agreed that the idea of framework on occupational safety, health and environment (OSHE) in order to design a safe school concept is very interesting and might be very useful in the future to minimize the incident cases in school. This paper also will be illustrated through poster and video presentation for more further understanding.